THE DEVELOPMENT OF CHEMISTRY ADVENTURE (CHEMTURE) GAME AS LEARNING MEDIA ON CHEMICAL BONDING MATTER FOR HIGH SCHOOL STUDENT (Universitas Negeri Surabaya, 2019)
The aim of the research is to produce feasible Chemistry Adventure game as a learning media on Chemical Bonding matter for high school students. The feasibility are reviewed based on validity, practicality, and effectiveness of Chemistry Adventure game. The validity is determined from results of the assessment of contents and construct validity by three validators, the practicality is determined by results of activities observation and response questionnaire of student, while the effectiveness is determined from the learning outcome of students and interest in learning of students. This research is development research using Research and Development (R&D) design with one group pretest and posttest method which is limited trial test was conducted to 33 students of 10th grade of SMAN 1 Sidoarjo, East Java. The result of content and construct validity for every aspect obtained percentage of 73.33% to 86.67% in valid to very valid category. The result of activity observation of students shows relevant activity that obtained percentage of 88.06% and response of students obtained percentage of 89%. Learning outcome of students shows classical completeness of 90.91% and interest in learning of students was classified as high category with average percentage of 83.76%. Based on the research result can be concluded that Chemistry Adventure game is feasible to be used as learning media.Keywords: Game, Chemistry Adventure, Chemical Bonding